A study of special education teachers' and administrators' perception of behavior problem - Pulian, Zenaida Pinga 1944- (College of Education, University of the Philippines Diliman, 1977)
This study is designed to find out the perception of special education teachers and administrators regarding the degree of seriousness of the different behavior problems through the use of a questionnaire. The 61 subject respondents in this study were the teachers and administrators of three government special schools in Metro Manila for children who have emotional or social problems. Through the use of Kendall Coefficient of Concordance, the results of the study revealed that the respondents were not in agreement in their perception of the degree of seriousness of the behavior problems. It showed a discrepancy in the criteria used for looking at the different behavior problems.